Review and Comments for the Development of Point Defect‐Controlled CZ‐Si Crystals and Their Application to Future Power Devices. Issue 10 (27th December 2018) - Hourai, Masataka; Nagashima, Toru; Nishikawa, Hideshi; Sugimura, Wataru; Ono, Toshiaki; Umeno, Shigeru
Abstract : Development of point defect‐controlled Czochralski silicon (CZ‐Si) crystal growth technology by v/G control, i.e., the ratio of growth rate (v) to the axial temperature gradient (G) in the crystal near its melting point, is reviewed and nitrogen‐ and hydrogen‐doping technologies are proposed for 300‐mm magnetic‐field‐applied CZ‐Si (MCZ‐Si) crystals free of grown‐in defects with very low oxygen for application to future silicon power devices such as insulated gate bipolar transistors (IGBTs). Using a hot zone with a uniform G distribution in a crystal radial direction, v/G is maintained by controlling v of around the critical value at which the amount of vacancies is balanced with that of self‐interstitials so that the generation of grown‐in defects, such as voids and dislocation clusters, are suppressed. Nitrogen‐doping or hydrogen‐doping technology combined with v/G control also enables the enlarging of the process window for grown‐in defect‐free MCZ‐Si crystals that can be used as an alternative material to floating zone‐Si crystals. The advantages and disadvantages of both technologies are discussed from the view point of crystal quality required to guarantee higher performance of future IGBTs. Abstract : Point defect‐controlled CZ‐Si crystal growth technology is reviewed by manipulating the v/G ratio, where v is the growth rate and G is the axial temperature gradient in crystals. Nitrogen‐ and hydrogen‐doping technologies combined with v/G control are proposed for 300‐mm MCZ‐Si crystals free of grown‐in defects with very low oxygen for application to future Si power devices such as IGBTs.